(untitled) (Eurasian Research Bulletin, 2023)
Dysfunctional changes in the upper respiratory tract in most cases develop as a postburn pathology. (1,2,12). After a burn, in 30-40% of patients, the general condition worsens and vital organs fail. (,3,6,8,11,13,16). The most important factors that damage the mucous membrane of the respiratory tract during IT are various combustion products in a confined space. The development of mucosal edema is primarily dependent on mediators such as histamine, bradykinin, prostacyclin and bronchospasm, and pulmonary vascular resistance is associated with the release of thromboxane and complement components (8.15).